Cell totipotency: molecular features, induction, and maintenance. Issue 2 (15th February 2015) - Lu, Falong; Zhang, Yi
Abstract: In mammals, pluripotent stem cells can give rise to every cell type of embryonic lineage, and hold great potential in regenerative medicine and disease modeling. Guided by the mechanism underlying pluripotency, pluripotent stem cells have been successfully induced through manipulating the transcriptional and epigenetic networks of various differentiated cell types. However, the factors that confer totipotency, the ability to give rise to cells in both embryonic and extra-embryonic lineages still remain poorly understood. It is currently unknown whether totipotency can be induced and maintained in vitro . In this review, we summarize the current progress in the field, with the aim of providing a foundation for understanding the mechanisms that regulate totipotency.